The Influence of Regional Financial Performance on Poverty Levels in Central Java Province - Komedi, Komedi; Prabowo, Hadi; Akbar, Bahrullah; Daraba, Dahyar (Journal of Governance, 2025)
Central Java Province has a large APBD; the poverty level in this region remains high and has not shown a significant decline. This raises questions regarding the effectiveness of budget allocations and the use of regional financial resources in poverty alleviation efforts. Thus, it is important to conduct research on how big the influence of the APBD as seen from regional financial performance is on poverty levels. This research uses a quantitative approach to analyze data obtained from 35 districts/cities in Central Java Province. The influence of regional financial performance on poverty levels in Central Java during the 2017-2022 period is shown by the coefficient of determination test (adjusted R-squared) of 0.146874 or 14.6874%. This means that financial performance, which includes the income growth ratio, In addition, regional governments are advised to propose transfer funds in the form of block grants for flexibility in budget allocation. Optimizing the Electronic-Based Government System (SPBE) is also important to support the implementation of the APBD. Finally, further research is needed to explore other factors that influence poverty levels in Central Java Province.